The Effect of Weblog on the Filipino Learners' Writing Performance - Rothelia Maria Ugsad (Philippine Association of Institutions for Research, Inc., 2017)
Writing is a daunting task for Filipino college students. However, in the midst of cyberspace and social networks, this study sought to determine the effect of the weblog as a motivational tool on the writing performance of Bachelor of Arts in Communication 1st year college students of Palompon Institute of Technology, Philippines. Using the pretest-posttest control group design, the students enrolled in Communication Skills II were randomly assigned to either the weblog group or the paper-and-pen group. A writing test was used both as a pretest and posttest, which was scored using Jacobs (1981) ESL Composition Profile. The data were treated using the mean and t-tests for both dependent and independent samples. Results revealed that the students' initial writing performance was more or less on the same level while the post writing performance of the weblog group was better than the paper-and-pen group. Students in both groups benefited considerably from the use of their respective writing tools, but weblog is a more motivating tool than the paper and pen in the development of the students' writing ability. Students then need a writing tool in whatever form to improve their writing ability, but they perform better if they use a weblog instead of paper and pen.